Relationship of individual psychological peculiarities of convicts with a tendency to auto-aggressive behavior - M. A. Sergeeva; L. F. Fursi; A. S. Kubekova (Вестник университета, 2020)
The article reflects the results of a study of the relationship between the individual psychological characteristics of convicts with a tendency to auto-aggressive behavior. The authors carry out a psychodiagnostic examination using 4 methods: a suicidal risk questionnaire T.N. Razuvaeva; mini-cartoon (abridged version of MMPI, Russian adaptation by V.P. Zaitsev and V.N. Kozyulya); questionnaire «Anxiety and depression» (K.K. Yakhin, D.M. Mendelevich); color test M. Luscher. The paper ascertains that the personality of convicts prone to auto-aggressive behavior is indeed characterized by certain individual psychological characteristics. These individual psychological characteristics can be divided into two groups: one group of individual psychological characteristics (demonstrativeness, social pessimism, maximalism, uniqueness, breaking cultural barriers) is associated with a tendency to an extreme form of manifestation of auto-aggressive behavior, that is, to suicide, and the other group of individual psychological characteristics (black color, depression, psychasthenia and schizoid) are characteristic of convicts who are prone to manifesting auto-aggressive behavior in the form of self-harm. On the basis of the study, recommendations were developed for the prevention and correction of convicts prone to auto-aggressive behavior